TINJAUAN YURIDIS PEMBERIAN REMISI UMUM DAN REMISI DASAWARSA TERKAIT PP NO. 99 TAHUN 2012 KASUS NARKOTIKA - Maurice Roger Siburian (JURNAL RECTUM: Tinjauan Yuridis Penanganan Tindak Pidana, 2019)
Remission of prisoners related to PP number 99 of 2012 narcotics cases at the Medan Class I Correctional Institution can be given if they have undergone 1/3 (one third) of the criminal period or have cooperated with law enforcement to uncover the case as evidenced by the issuance of a letter statement of justice collaborator (JC) by law enforcement (Polri, prosecutors, BNN). In writing this thesis, the author uses juridical normative research methods, namely research methods that refer to norms of norms and principles of legal principles contained in statutory regulations and decisions of court decisions and legal norms that exist in society and synchronization of a rule with other rules in a hierarchical manner. Based on research conducted by researchers at the Medan Class I Correctional Institution, that prisoners of narcotics cases related to PP number 99 of 2012 who received a general remission in 2015 in accordance with Letter of Kep envoy of the Minister of Law and Human Rights Number M.HH-114.PK.01.01.02 of 2016 concerning the granting of 2015 general remissions to criminal inmates and children related to article 34A paragraph (1) government regulation number 99 of 2012 dated June 27 2016 as many as 240 people.